Human Physiology (Laboratory Manual Fetal Pig Dissection) - R. Martin Terry (MC Graw Hill, 2007)
This edition has been completely renovated and all of the exercises have been carefully refined and updated to keep pace with the continuous changes in laboratory technology, vendor supply sources, and to address updates in computer-assisted instruction and biohazard health concerns. It can be used in conjunction with any human physiology textbook, and a wide variety of exercises support most areas covered in a one-semester human physiology course, so you can choose which exercises best meet your instructional goals.